ANALISIS KELAYAKAN TEKNIS DAN FINANSIAL PRODUKSI SOSIS JAMUR TIRAM PADA SKALA INDUSTRI KECIL (STUDI KASUS DI BUDIDAYA JAMUR TIRAM ‘WAHYU’ KOTA MOJOKERTO) - Meta Fitri Harlistaria; Wignyanto Wignyanto; Dhita Morita Ikasari (Department of Agro-industrial Technology, University of Brawijaya, 2012)
Sausage is a type of food which is popular in the market and often consumed by people, especially children and teenagers. Therefore, oyster mushroom can be turned into sausage and becomes a solution for the vegetarians to substitute the meat. The method used to analyze the technical aspects is an approach to the raw material availability. However, the method used to analyze the financial aspects is the calculation of HPP, BEP, and R/C Ratio. The production of oyster mushroom sausage will be done in UKM Wahyu Mojokerto with the capacity of 10 kg oyster mushroom per day which will produce 110 oyster mushroom sausages and the need of 11 vacuum packaging and 2 labors. The work hours start from 08.00 am to 1.40 pm for 5 days. The production process is carried out every one cycle per day by using the main machine that is sausage filler. The result of the oyster mushroom sausage production in UKM Wahyu is calculated from the financial aspects (HPP) Rp 1.666,75 with the selling price Rp 2.000,00. Therefore, the BEP is 13.308 units and Rp 26.617.544,51 while the R/C Ratio is 1,2. It means that the production of oyster mushroom sausage has met the standards of business efficiency that can be said to be profitable and viable. Key word: financial aspects, technical aspects oyster mushroom sausage.